ECONOMIC VALUE APPROACH TO COOKING OIL WASTE MANAGEMENT IN BUMDES PANGGUNG LESTARI, PANGGUNG HARJO, BANTUL, YOGYAKARTA - Sujatmika Sujatmika; Sri Kussujaniatun; Diah Lutfi Wijayanti; Anis Siti Hartati (Universitas Tidar, 2022)
The purpose of this study was to analyze the economic valuation of the use of used cooking oil in Bumdes Panggung Lestari, Panggung Harjo Village, Bantul. The research was conducted because the handling of externalities must be managed properly so as not to cause disturbances in community activities. Economic valuation is an attempt to give a quantitative value to economic activity, both on the basis of market value and non-market value. The method used in this research is an economic value approach which includes an opportunity cost and an economic valuation approach. The results show that the total economic value of using cooking oil is dominated by direct use-value. The results imply that the management of cooking oil waste can be a source of income for the local village community and can be an effort to control environmental pollution from cooking oil waste.